Deutschlands Einigung: Diplomatisches Kunstwerk, Einfache Rechtskonstruktion - Brauneder, Wilhelm (Pázmány Law Review, 2023)
The unification of Germany was achieved by the foundation of a federal state with a very unique struture due to the political possibilities and open to further developements. To give the impression of fullfilling a historcal mission traditional terms were used like ‚German Emperor‘ and ‚German Empire‘ for just created modern institutions. The centre of statehood, especially the judiciary and the administration, remained by the member states. Even the army consisted of their contingents. The souveranity oft he Empire was not hold by the emperor but by all the monarchs oft the member states together so to say in coownership. Despite the developement was headed by Prussia the unification was also a strong desire in all parts of Germany. The separation from Austria’s German provinces, which also belonged to the in 1866 ending German Confederation (Deutscher Bund), was taken in account.